2018
DOI: 10.1039/c8sc03005g
|View full text |Cite
|
Sign up to set email alerts
|

The special role of B(C6F5)3 in the single electron reduction of quinones by radicals

Abstract: In the presence of two molar equiv. of B(C6F5)3p-benzoquinone reacts with persistent radicals TEMPO, trityl or decamethylferrocene by single electron transfer to give the doubly O-borylated benzosemiquinone radical anion with TEMPO+, trityl cation or ferrocenium counter cations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 43 publications
(27 reference statements)
3
18
0
Order By: Relevance
“…Then, BCF radical anions react with benzoyl peroxide (BPO), or another Lewis base, to form the counterion [PhC(O)O-B(C 6 F 5 ) 3 ] − , yielding the salt [Cp 2 *Fe] + : [PhC(O)O-B(C 6 F 5 ) 3 ] − (Scheme 1). 23 Similar oxidation reactions have been demonstrated using oxygen 21 or quinones 24 as the weak Lewis base. The ability of Lewis acid–base pairs to carry out single electron transfer reactions suggests a route to increase the efficiency of BCF as a dopant for organic semiconductors.…”
Section: Introductionsupporting
confidence: 54%
“…Then, BCF radical anions react with benzoyl peroxide (BPO), or another Lewis base, to form the counterion [PhC(O)O-B(C 6 F 5 ) 3 ] − , yielding the salt [Cp 2 *Fe] + : [PhC(O)O-B(C 6 F 5 ) 3 ] − (Scheme 1). 23 Similar oxidation reactions have been demonstrated using oxygen 21 or quinones 24 as the weak Lewis base. The ability of Lewis acid–base pairs to carry out single electron transfer reactions suggests a route to increase the efficiency of BCF as a dopant for organic semiconductors.…”
Section: Introductionsupporting
confidence: 54%
“…Analogous reactions using Zn(C 6 F 5 ) 2 as the Lewis acid were also reported . Erker et al subsequently reported the reactions of the transient radical [B(C 6 F 5 ) 3 ] .− with quinones while we showed the cleavage of peroxides with the FRP derived from Mes 3 P and B(C 6 F 5 ) 3 . Müller, Oestreich and co‐workers reported the generation of silyl‐radicals and the phosphonium radical cations from the reactions of silylium cations with triarylphosphines .…”
Section: Methodsmentioning
confidence: 93%
“…[22][23][24] Interestingly, it has been shown by Stephan and Erker that the combination of two equivalents of B(C 6 F 5 ) 3 with the electron acceptor p-benzoquinone C 6 H 4 O 2 is able to oxidize decamethylferrocene to its cation. 25,26 Depending on the stoichiometry [C 6 H 4 O 2 •2 B(C 6 F 5 ) 3 ] −/2− mono-or dianions are obtained. By choosing other Lewis acids, the oxidation power of the system can be tuned.…”
mentioning
confidence: 99%